3(x+1)x+4(x+3)=22

Simple and best practice solution for 3(x+1)x+4(x+3)=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)x+4(x+3)=22 equation:


Simplifying
3(x + 1) * x + 4(x + 3) = 22

Reorder the terms:
3(1 + x) * x + 4(x + 3) = 22

Reorder the terms for easier multiplication:
3x(1 + x) + 4(x + 3) = 22
(1 * 3x + x * 3x) + 4(x + 3) = 22
(3x + 3x2) + 4(x + 3) = 22

Reorder the terms:
3x + 3x2 + 4(3 + x) = 22
3x + 3x2 + (3 * 4 + x * 4) = 22
3x + 3x2 + (12 + 4x) = 22

Reorder the terms:
12 + 3x + 4x + 3x2 = 22

Combine like terms: 3x + 4x = 7x
12 + 7x + 3x2 = 22

Solving
12 + 7x + 3x2 = 22

Solving for variable 'x'.

Reorder the terms:
12 + -22 + 7x + 3x2 = 22 + -22

Combine like terms: 12 + -22 = -10
-10 + 7x + 3x2 = 22 + -22

Combine like terms: 22 + -22 = 0
-10 + 7x + 3x2 = 0

Factor a trinomial.
(-10 + -3x)(1 + -1x) = 0

Subproblem 1

Set the factor '(-10 + -3x)' equal to zero and attempt to solve: Simplifying -10 + -3x = 0 Solving -10 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -3x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = 0 + 10 -3x = 0 + 10 Combine like terms: 0 + 10 = 10 -3x = 10 Divide each side by '-3'. x = -3.333333333 Simplifying x = -3.333333333

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-3.333333333, 1}

See similar equations:

| 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) | | 13x-4x=-63 | | 3y+4z=9fory | | 8x=6y+5 | | 22-6y+y^2-14=0 | | 83=15+2(x) | | -8a=-8b | | (3)(2x-4)+2(2x-4)-x=-17 | | 12=15*Z-1/5 | | x+(-40)=y | | X^2+4x-62.5=0 | | 15=5+9(3) | | b+-4=-4 | | -5x=-5y | | g/3-0.9=-.4 | | 85=17p | | 7x^4z^3/28y^3 | | (6x+2)(3x+4)=64 | | 5y(y+2)= | | -36x-36=0 | | 3(2x+4)-2x=3(2-4x) | | 5[m+4]=-2[-4-m]+3 | | (5-5):(1/5) | | 2*3+5=360 | | 12v+14+-10v=80 | | 3x+63+6x+12=180 | | 5-5:1/5 | | ln(x-1)+ln(x+4)=ln(2(x+1)) | | 5-5/1/5 | | 11=-20+121 |

Equations solver categories